Quality Analysis Of Honey Mallawa Parameters Based On Physical Chemistry - Sukmawati, Sukmawati; Noor, Alfian; Firdaus, Firdaus (Indonesian Journal of Chemical Research, 2015)
Analysis of chemical physics parameters on Mallawa honey has been done as density, viscosity, HMF, reducing sugars, sucrose and enzyme diastase. The results obtained showed that the average weight of honey Mallawa is 1.373 g / mL, the viscosity of 10.9651 P, HMF amounted to 49.120 mg / Kg, reducing sugar amounted to 70.752% w/w, sucrose at 3:25 w/w and enzymes diastase of 3.805 DN, This is according with ISO and IHC (International Honey Commition) that category Honey Mallawa still good enough for consumption